AMENDMENTS TO THE LAW OF UKRAINE «ON ALL-UKRAINIAN REFERENDUM» AND SOME PRECAUTIONS REGARDING THEIR APPLICATION IN PRACTICE - Mikhnevych, Liudmyla; Hryhorenko, Artem (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
As the title implies the article describes the relevance of the adopted Law of Ukraine «On the All-Ukrainian Referendum» for Ukrainian legislation. In the process of emergence as a European state, Ukraine needs effective implementation of the Law of Ukraine «On the All-Ukrainian Referendum». This law regulates the proper legal basis of the institution of the all-Ukrainian referendum. An important role is played by the subject of the all-Ukrainian referendum regarding the resolution of issues of national importance, changes in the territory of Ukraine. The relevance and significance of this study is also due to the need to rethink the traditional understanding of the concept of the all-Ukrainian referendum, changes in the circle of referendum subjects, and the legal status of the Central Election Commission in this process. Purpose: analysis of individual provisions of the Law of Ukraine «On the All-Ukrainian Referendum», highlighting gaps in national legislation that arise in connection with the application of this law in practice Research methods: used methods of analysis, comparative and legal analysis, cognitive and analytical. The results: it was concluded that the Law of Ukraine «On the All-Ukrainian Referendum» was developed in accordance with the requirements of the Constitution of Ukraine. The main aspects of the legislative changes are the regulation of legal relations related to the initiation, appointment (proclamation), preparation, holding, establishment of results and legal consequences of the all-Ukrainian referendum. Discussion: the need to make changes to some norms of the Law of Ukraine «On the All-Ukrainian Referendum» in the part of holding the all-Ukrainian referendum on changing territories.